MOTIVASI KONSUMEN DALAM MEMILIH JASA SENAM BAYI DI ROCKSTAR GYM - Muhammad Awaludin Setiawan (Jurnal Manajemen dan Bisnis Madani, 2019)
The purpose of this study is to analyze the motivation of consumers in choosing baby gymnastics services at Rockstar Gym. This analysis uses McGuire's psychological motivational theory. The research method used is descriptive with qualitative approach. Resource persons in this study are parents who include their infants to a baby gym class by conducting semi-structured interviews with a total of 20 questions. The results of this study indicate that the motivation of consumers to choose baby gymnastic services is to get encouragement from sources of information trusted through, 1) articles and blogs, 2) social media, 3) advice from doctors, and see directly, 4) have knowledge of the need (6) to express the development of the baby from the side of brain intelligence and from the side of health, 7) want to register the baby to physical movement activities, 8) worry about the world of children, children now, 9) want to express their identity to people around by showing their closeness with the baby, 10) want to develop socialization and spur the rough motor development of the baby.